ANALYTICAL METHODS IN ARCHAEOMETRY: STUDY OF SUPPORT MATERIAL - Rodica Mariana Ion; Radu Claudiu Fierascu; Irina Dumitriu (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry, 2011)
The application of some analytical techniques developed initially in materials science (techniques based on physical-chemical phenomena) in the study of art and archaeological objects offers the historian and archaeologist quantitative information that can prove useful in order to better understanding of ancient society. The preservation of material culture for future generations with the best possible fidelity requires in-depth knowledge, to aid the most suitable restoration, conservation, storage, and eventual museum display. The use of analytical techniques often proves useful for the specialists in conservation and/or restoration due to the valuable information given (composition, state of degradation, and so on). This paper describes the use of some analytical techniques (X-ray fluorescence - XRF, inductively coupled plasma - atomic emission spectrometry - ICP-AES, Fourier transformed - infrared spectroscopy - FTIR) for analyzing compositions of artifacts.